Fuel Arc Furnace (FAF) for Effective Scrap Melting From EAF to FAF - Toulouevski, Yuri N.; Zinurov, Ilyaz Y.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book presents a new electric arc furnace process and discusses potential for developing a steelmaking aggregate of the new generation, namely the Fuel Arc Furnace based on existing shaft furnaces. It also reviews the history of developing various types of furnaces with the scrap preheating and flat bath advantages of these furnaces, identifying their disadvantages and presenting methods of eliminating them.
The history of furnaces with scrap preheating and flat bath Advantages of these furnaces -- Disadvantages of furnaces with scrap preheating and flat bath Advantages of these furnaces -- Causes of these disadvantages and methods eliminating them -- Fuel Arc Furnace (FAF).
Keywords: Metals; Engineering design; Chemistry, Technical; Energy policy; Energy and state; Metals and Alloys; Engineering Design; Industrial Chemistry; Energy Policy, Economics and Management